Effectiveness of prayer in reducing anxiety in cancer patients - Camila Csizmar Carvalho; Erika de Cássia Lopes Chaves; Denise Hollanda Iunes; Talita Prado Simão; Cristiane da Silva Marciano Grasselli; Cristiane Giffoni Braga (SciELO, 2014)
Objective: To evaluate the effect of prayer on anxiety in cancer patients undergoing chemotherapy. Method: Quasi-experimental study, with pre and post-intervention. Twenty patients admitted to treatment of continuous intravenous chemotherapy were recruited. The volunteers were evaluated through interviews using a questionnaire of sociodemographic, clinical and spiritual characteristics, the Index of Religiosity Duke University and the State-Trait Anxiety Inventory. Vital signs were measured and collected salivary cortisol. The intervention was applied prayer and data collection occurred in three phases: first collection (baseline), pre and post-intervention. Results: The data found between the pre and post-intervention samples showed different statistically significant for state anxiety (p= <0.00), blood pressure (systolic, p=0.00, diastolic, p=<0.00) and respiratory rate (p=0.04). Conclusion: Prayer, therefore, proved to be an effective strategy in reducing the anxiety of the patient undergoing chemotherapy.